'Pinkwashing' the radical‐right: Gender and the mainstreaming of radical‐right policies and actions. (15th March 2021) - BEN‐SHITRIT, LIHI; ELAD‐STRENGER, JULIA; HIRSCH‐HOEFLER, SIVAN
Abstract: Across the globe, women are increasingly more visible as leaders and activists in radical‐right parties and movements. Does women's visibility in radical‐right politics, both institutionalized and non‐institutionalized, affect public acceptance of radical‐right agendas? The present paper proposes a 'radical‐right gender mainstreaming model', arguing that women in radical‐right politics are perceived by the general public through a prism of feminine gender stereotypes, which counteract radical‐right parties' and movements' masculine stereotypes, thus 'softening' their image and making them more acceptable to the general public. Across four experimental studies conducted in the Israeli context, we find strong evidence that women's visibility as radical‐right parliamentary representatives (Studies 1a and 1b) and as radical‐right political activists (Studies 2a and 2b) increases acceptance of and support for these parties' and movements' agenda, particularly among women. We further demonstrate that these effects are mediated by the attribution of feminine stereotypes (warmth) to women versus men political actors. Implications of these findings are discussed.